Hahnemann’s Life–Some Insights (Homoeopathy for All, 2025)
There is much to learn from the Great Healer, the Master of Homoeopathy, not only about homoeopathy but also as a person – his intelligence, his dedication, his perseverance, his sincerity, his philanthropic attitude and much more. On his birth anniversary each year, it gives us an opportunity to remember Dr. Samuel Hahnemann and talk about his achievements. His fascinating life history and the amount of work that he was able to accomplish during his life span is amazing and unbelievable.
Keywords: Healer; Homeopathy; Cured; Suffer; Risk